Efektivitas Penerapan Strategi Pembelajaran Aktif Synergetic Teaching Ditinjau Dari Motivasi Belajar Peserta Didik - Arfin, Arfin; Jamaluddin, Jamaluddin; Fitriani, Fitriani; Jaya Nur, Makmur (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
This research aims determine that efektiveness of active learning synergetic teaching, Synergistic active learning is a learning strategy that combines two different learning methods simultaneously; In this research, lecture and reading methods were combined. Learning motivation is the drive within a person to carry out learning activities to achieve goals. Quantitative research methods, types of experiments, experimental design, and one group pretest-posttest approach. Class VIII B students of SMP Negeri 3 Sinjai were the research subjects. Learning motivation questionnaires, learning implementation observation sheets, and documentation are data collection methods. In this research, the data analysis technique used is the t-test (paired sample t-test). The results showed that students had greater motivation to learn both before and after treatment by implementing synergistic active learning strategies. Therefore, this approach is effective for use in learning. The research results show that students' learning motivation increases when synergistic active learning strategies are implemented. The average value was 85.17 with a standard deviation of 7.861 and a variance of 61.79, and rose to 87.57 with a standard deviation of 7.38 and a variance of 54.46. However, based on the results of the hypothesis test, it was found that the tcount value was -5.475, which was smaller than the ttable value of 1.69913 and the significance value was 0.000, which was less than 0.05.